PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS PENEMUAN TERBIMBING (GUIDED DISCOVERY) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS XII IPA SMA PADA MATERI SUBSTANSI GENETIKA - ESTUNINGSIH, SILVIA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Chromosome, DNA, and gene are concept that complex and complicated. Learn methode that used to explain this concept are run of one direction, it make the student more memorize rather than understanding a concept, so their learning outcome is low. Baesd of that problem, the direction of this research is to develop the student worksheet based on guided discovery, so can increasing student learning exhaustiveness. The definite experiment do at science thir grade of MA Matholiâ€™ul Anwar Lamongan. The type of this research is development research based on 4-D development procedure. The result of this research indicates student learning exhaustiveness namely 83%. Â Keyword: student worksheet, guided discovery, genetic substance.